Marketing strategies and halal labels on Non-Food Products in Indonesia - Nurfadhilah, Nurfadhilah; Salmayanti; Tenriyati; Alimuddin, Andi Arnita (Jurnal Manajemen Bisnis, 2024)
For Muslims, whether a product is haram or halal is fundamental and very important. The halal label on a product can now be categorized as an important thing due to the high number of Muslim populations in the world. This increase is accompanied by increasing awareness of consuming halal products, especially in Indonesia. Apart from food products, the halal label has also become a trend for other non-food products, such as cosmetics, medicines, toiletries, perfume, etc. This research aims to determine the relationship between marketing mix variables and halal labels on purchasing decisions for non-halal products in Indonesia, either partially or simultaneously. This research used a sample of 100 Muslims spread throughout Indonesia. Data collected in the form of a questionnaire was analyzed using multiple linear regression analysis with the help of the SPSS application. The research results show that partially, the product, place and halal label variables have a positive and significant effect on purchasing decisions, while price and promotion have no effect. However, when all variables were tested together, the results were found to have a positive and significant effect.